The Potential of Digital Games as a Medium for Learning Pancasila and Civic Education: Efforts to Build Ecological Awareness in Support of Sustainable Development - Eli Karliani; Eriawati Eriawati; Ali Sunarno; Dewi Rakhmawati; Fenroy Yedithia (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2025)
The purpose of this study is to analyze students' views on the potential of digital games as a learning medium and the opportunities to use them to build ecological awareness in support of sustainable development. This study used a quantitative approach involving 196 high school students in Palangka Raya City. The results of the study show that 51 percent of students are interested in game-based learning, 73.5 percent of students say that games can be used as a means of delivering material, 77.6 percent of students have learned using games both formally and informally, and 87.8 percent of students are willing to try educational games for learning in the future. The use of digital games as a learning medium for Pancasila and citizenship education can shape students' ecological awareness in the context of sustainable development. Obstacles to implementing digital games as a learning medium to shape ecological awareness include low levels of teachers' digital literacy, limited school infrastructure, and limited availability of environment-based educational games.